Quantification of the pulmonary vascular obstruction index on ventilation/perfusion lung scintigraphy: Comparison of a segmental visual scoring to the Meyer score - Le Pennec, Romain; Tromeur, Cécile; Orione, Charles; Robin, Philippe; Le Mao, Raphaël; Gut-Gobert, Christophe; Le Gal, Grégoire; Salaün, Pierre Yves; Le Roux, Pierre Yves (Frontiers in Medicine, 2022)
Introduction: Quantifying the pulmonary vascular obstruction index (PVOI) is essential for the management of patients with pulmonary embolism or chronic thromboembolic pulmonary hypertension (CTEPH). The reference method for quantifying the PVOI with planar lung ventilation/perfusion (V/Q) scintigraphy is the Meyer score, which was validated using pulmonary angiography as a reference standard. However, it is complex to use in daily practice. In contrast, a rapid and fast quantification method consists in estimating the PVOI based on the number of segmental perfusion defects. However, the accuracy of this method has never been evaluated. In this study, we aimed to compare PVOI quantification on planar V/Q scintigraphy assessed by a segmental visual scoring (SVS) to the Meyer score. Methods: The eligible study population consisted of consecutive patients who underwent planar V/Q scan for CTEPH screening. A central review was performed by three nuclear medicine physicians. PVOI was assessed by summing the number of segmental perfusion defects or equivalent (2 sub-segments = 1 segment = 5%) and by Meyer’s method. The two interpretations were performed six months apart. A Spearman rank correlation coefficient was calculated to evaluate correlation between the two measurement methods. An intra-class correlation (ICC) was calculated to assess agreement. A Bland et Altman plot analysis was used to evaluate agreement between the two measurements Results: A total of 226 V/Q scans were interpreted. Spearman rank correlation coefficient between SVS and Meyer was 0.963 (95%CI 0.952-0.971) for mismatched perfusion defects and 0.963 (95%CI 0.953-0.972) for perfusion defects regardless of ventilation. Intra-class correlation (ICC) for agreement was 0.978 (95%CI 0.972-0.983) for mismatched perfusion defects and 0.968 (95%CI 0.959-0.976) for perfusion defects regardless of ventilation. In Bland & Altmann analysis, the mean difference between the SVS method and the Meyer score was 0.42 and 0.61 for the mismatched or matched evaluation, respectively. Conclusion: Our study shows a high correlation, and low differences in PVOI quantification when using a segmental visual scoring (SVS) as compared to the Meyer score. The SVS has the great advantage to be easy and rapid to apply in daily practice